Computer simulation of wagon body bearing structure dynamics during transportation by train ferry - Ловська, Альона Олександрівна (Eastern-European Journal of Enterprise Technologies, 2015)
The increased pace of Ukraine’s integration into the system of international transport corridors necessitates the development of combined transport systems. Train ferry services are one of the most promising in this direction. To ensure the movement safety of wagons on train ferries, estimating the forces acting on them in a rough sea is needed. An analysis of the literature, describing the features of the sea transportation of wagons, led to the conclusion that the issue has been neglected to date. In this connection, a computer model of the strength of the fragment of the train ferry with the wagon bodies, placed on its decks, which takes into account the range of the main forces acting on the ship and wagons in a rough sea was developed. The computer simulation results allow to determine the magnitude of dynamic loads on the wagon body bearing structure during transportation by train ferry. The studies may be taken into account when designing new-generation wagons at wagon works that will increase the motion safety of wagons in the sea.